Spatial variation of zero fruits/vegetables consumption and associated factors among children aged 6–23 months in Ethiopia: geographical weighted regression analysis - Tilahun, Werkneh Melkie; Simegn, Mulat Belay; Geremew, Habtamu; Gebreegziabher, Zenebe Abebe; Abay, Lamrot Yohannes; Tesfie, Tigabu Kidie (Frontiers in Nutrition, 2024)
Background: After six months, nutrient-dense, varied diets containing fruits and vegetables are crucial to supplement breastfeeding. Like many other low-income countries, Ethiopia has very low FV consumption. Zero vegetable or fruit (ZVF) consumption has been shown to significantly raise the risk of non-communicable diseases and has been ranked among the top 10 risk factors for mortality. And it is associated with poor health, an increased risk of obesity, and a higher risk of non-communicable diseases. Thus, this study's goal was to investigate the spatial distribution of ZVF consumption and its spatial determinants among children aged 6-23 months in Ethiopia.A cross-sectional study design was employed. A total of 1489 weighted samples were included from kids' datasets from the 2019 Ethiopian mini-demographic and health survey.STATA version 16, ArcGIS version 10.8, Kuldorff's SaTScan version 9.6, and MGWR version 2.0 software were used for analysis. Spatial regression analyses (geographical weighted regression and ordinary least squares analysis) were conducted. Models were compared using AICc and adjusted R 2 . A P-value of less than 0.05 was used to declare statistically significant spatial predictors, and the corresponding local coefficients were mapped.The spatial distribution of ZVF consumption among children aged 6-23 months was nonrandom in Ethiopia. Spatial scan analysis revealed a total of 120 significant clusters. Maternal education, wealth status, age of the child, place of delivery, number of under-five children in the house, and current pregnancy status were significant predictors of the spatial variation of ZVF consumption.Significant geographic variation in ZVF consumption was found in this study throughout Ethiopia's regions. Significant predictors of the spatial variation in ZVF consumption were maternal education, wealth status, child age, place of delivery, number of under-five children in the home, and status as a pregnant woman at the time of birth. Therefore, in order to improve children's adequate consumption of fruit and vegetables, area-based interventions that can consider these significant factors into account are needed.